PPIC IMPLEMENTATION IN FULFILLING ISO 9001: 2015 REQUIREMENTS - Lala Hucadinota Ainul Amri; Mukhyidin Djaiz; Nada Zata Sharfina (Kreator, 2021)
A company needs to improve performance, especially in terms of quality in the effort to defend itself and compete with other companies. One of the ways the company in improving its quality is by improving the Quality Management System that has been used. The implementation of QUALITY Management System ISO 9001:2015 in the company is an appropriate step to win competition, especially in conducting print planning in the printing industry. PPIC is a department that has a very important function as Product Planning and Control of material supplies in every activity related to production activities in printing, so there needs to be the implementation of an integrated and sustainable Quality Management System. Fulfillment of ISO requirements is an important step that must be taken in order for the company to officially receive iso certificate This study uses descriptive writing method, using observation data collection method, interview, and library study. Implemented in iso 9001:2015 certified companies. The results showed ppp or PPIC units or other designations in the company have met the requirements of ISO 9001:2015. In the implementation of the fulfillment of the requirements there are some obstacles that can be overcome such as administrative processes that have not been implemented properly. In addition, the supporting factor for the implementation of the most important requirements is the full support of management.Keywords— PPIC, ISO 9001:2015, Quality Management System